Planktothricoides-dominated blooms drive abnormal lipid metabolism and pathogens enrichment in the intestine of Eriocheir sinensis - Tong Li; Yongxu Cheng; Zhiyuan Yao; Yunfei Sun; Xiaozhen Yang; Wenwen Xiao; Demin Zhang; Huajun Zhang (Aquaculture Reports)
The Chinese mitten crab (Eriocheir sinensis, CMC) is of significant economic importance to China's aquatic industry. However, the prevalence of Planktothricoides-dominated cyanobacterial blooms (CBs) pose a substantial threat to this aquaculture sector. Despite their impact, there is limited understanding of how these CBs affect the digestive systems of CMCs. This study aims to investigate the effects of CBs dominated by Planktothricoides on CMC growth, intestinal bacterial communities, metabolism, and digestive enzyme activity. Our findings indicate that CBs dominated by Planktothricoides impede CMC growth and significantly alter immune and digestive enzyme activities. Notably, a decline in the richness and Shannon diversity of the intestinal bacterial community were observed, along with shifts in its structure and composition. The abundance of Epsilonbacteraeota, a group containing various conditional pathogens, reached 21.40 % at the family level in the CB group. A total of 26 bacteria were identified as potential pathogens in the CMC intestine. While immune activities demonstrated a strong correlation with potential pathogens, digestive enzyme activities were less correlated. Furthermore, CBs significantly impacted the metabolic pathways in the CMC intestine, leading to a marked reduction in several metabolites involved in lipid metabolism. In conclusion, this study focuses on the impact of CBs in natural environments on the digestive system of CMCs. It fills the knowledge gap regarding the actual negative effects of CBs on CMCs. Urgent interventions are warranted to support the prevention and control of CBs in CMC culture.